SPECIFIC NEUROPROTECTIVE EFFECTS OF MANUAL STIMULATION OF REAL ACUPOINTS VERSUS NON-ACUPOINTS IN RATS AFTER MIDDLE CEREBRAL ARTERY OCCLUSION - Li, Ling Xin; Fan, Xiao Nong; Meng, Zhi Hong; Shi, Xue Min; Luo, Ding; Zhang, Ya Nan (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
The objective of this study was to investigate the effectiveness and specific effects of acupuncture on ischemic-induced damage in rats after permanent middle cerebral artery occlusion. Cerebral ischemia was induced by middle cerebral artery occlusion in male Wistar rats. The rats were divided into the following 4 groups: normal controls, ischemic, real acupuncture-treated (Shuigou, DU26), and non-acupoint-treated groups. On the third postoperative day, neurological deficit scores, cerebral blood flow, infarction volume, and neuronal cell death counts were measured. In the real acupuncture-treated group, the neurological deficit scores and cerebral blood flow were improved (p < 0.05) and the infarction volume and neuronal cell death counts were reduced (p < 0.01) compared to the ischemic and non-acupoint-treated groups. The present study demonstrated that real acupuncture was effective against focal ischemia-induced damage in rats after middle cerebral artery occlusion, and the effects were specifically related to the right needling location.